Neurocognitive Impairment and Associated Factors Among Elderly in the Bahir Dar City Administration, Northwest Ethiopia - Fekadu, Betelhem; Tareke, Minale; Tadesse, Meseret; Anbesaw, Tamrat (Frontiers in Aging Neuroscience, 2022)
Abstract Background: Neurocognitive impairment is a widely common problem in the elderly. It encompasses mild and major cognitive impairment which will lead to disability and increase the risk of death. It also compromises the quality of life of the patient and also it has a burden on the family and society as a whole. However, there is a paucity of information concerning neurocognitive impairment among the elderly group in Ethiopia. This study aimed to assess the prevalence of neurocognitive impairment and associated factors among the elderly in Bahir Dar city, Ethiopia 2020. Methods: A community-based cross-sectional study was conducted among 423 respondents using a simple random sampling technique from June 1 to 30, 2020. Neurocognitive impairment was measured using the Mini-Mental State Exam adjusted cut-off point (presence or absence) by the level of education of the participants. Data were inter to epi data version 4.62 and exported to SPSS version 23 for analysis: descriptive statistics were used for summarization and presentation and binary logistic regression for a measure of association between exposures and outcome variable. Results: The prevalence of neurocognitive impairment was 42.1%. Has no spouse (AOR=1.76, 95%CI;1.08,2.86), having depression (AOR=3.04, 95%CI;1.80, 5.14), lifetime alcohol use (AOR=2.90, 95%CI;1.19, 7.07), and having low family support (AOR=3.07, 95%CI;1.35,6.96) and moderate family support (AOR=1.83; 95%CI;1.10, 3.06) were significantly associated with Neurocognitive impairment. Conclusion and recommendation: The prevalence of neurocognitive impairment was high in Bahir Dar city administration. Neurocognitive impairment was shown significant association with no spouse, depression, alcohol use, and low and moderate family social support. It is important to give concern for old age with comorbid mental illness and also to strengthen social support systems to prevent and manage neurocognitive impairment.